Efeitos toxicológicos neonatal, transgeracional e crônico de piretroides em Caenorhabditis elegans - Tamagno, Wagner Antonio (2022)
The extensive use of domestic and agricultural insecticides to control domestic, crop and even zootechnical pests has been growing in recent years. One of the main classes used in the composition of insecticides are the pyrethroids. These compounds have low neurotoxic action in humans, however exposure may increase predisposition to oxidative and neurodegenerative conditions. Caenorhabditis elegans is a soil worm widely known and used in biochemical, pharmacological and toxicological research due to its low cost, easy handling, wide translational index and rapid development. Thus, the objective of this work was to evaluate the toxic effect of four different insecticides based on pyrethroids in three different exposure protocols in C. elegans (transgenerational, neonatal and lifespan). Behavioral, biochemical biomarkers and the pattern of fluorescent expression of proteins from the antioxidant system and PolyQ40::YFP were evaluated. Finally, it could be concluded that pyrethroids have different mechanisms of interference in the animal organism, but what most draws attention is the transgenerational toxicological effect that seems to be related to the increased expression of mutated isoforms of the huntingtin protein and reduced activity from AChE. These findings highlight a greater predisposition to the onset of neurodegenerative and neurotoxic conditions in children of exposed parents (F1). In addition, several behavioral biomarkers were similarly altered in cross-generational and chronic exposures, however the physiological reasons altered by pyrethroids are related to different mechanisms of action. We highlight the increased risk of early development of Huntington's disease in a transgenerational way in genetically predisposed individuals.